Ceratomyxa drepanopsettae in the gallbladder of Atlantic halibut, Hippoglossus hippoglossus, from the northwest Atlantic Ocean - Morrison, C M; Martell, D J; Leggiadro, C; O'Neil, D (Folia parasitologica, 1996)
Trophozoites of Ceratomyxa drepanopsettae Averintsev, 1907 (Myxosporea: Ceratomyxidae) containing prominent refractile granules were found in the gallbladders of all but one of eight halibut, the exception being a single juvenile. They ranged in shape and size from globular forms 5-10 micron in diameter, to rounded structures with pseudopodia and one or more processes that were up to 500 micron in length and packed with refractile granules. Some trophozoites were free in the bile, while others were attached to the epithelium of the gallbladder wall by pseudopodia which extended between the microvilli. Many free trophozoites were attached to each other by septate junctions between their pseudopodia. There were small cylindrical papillae on the surface of the trophozoites, and the rounded portions contained two vegetative nuclei, generative cells (some attached by junctions) and, in many cases, feeding vacuoles. During sporogony, a binucleate sporoplasmic cell and the capsulogenic cells of some sporoblasts were engulfed by valvogenic cells before they began to differentiate; whereas other sporoblasts consisted of six cells attached to each other, two being capsulogenic cells containing external tubes, two sporoplasmic cells and two valvogenic cells. There was a septate junction around the opening of the rounded polar capsule of the spore, between the capsulogenic and valvogenic cell. Sporoplasmosomes appeared to form in smooth membraned vesicles, possibly part of the Golgi apparatus. Spores had thin, delicate membrane, and elongate shell-valves, most of which were asymmetric, and bent or folded. A sporoplasm extended on either side of the distinct, straight suture line, but did not penetrate into the valves.
Keywords: Atlantic Ocean; Male; Fish Diseases; Gallbladder; Eukaryota; mužské pohlaví; protozoální infekce zvířat; Atlantský oceán; platýsi; Flatfishes; Animals; Protozoan Infections, Animal; ženské pohlaví; zvířata; nemoci ryb; Spores; žlučník; spory; Female